A note on ethnicity and identity among the UK born population in Understanding Society - Alita Nandi; Lucinda Platt (University of Essex, Institute for Social and Economic Research (ISER), 2014)
In this note we take a first look at how the UK born identify across different dimensions (ethnicity, religion, political beliefs and region), to what extent the strength of attachment across these prescribed and elective identities strengthen or substitute each other and how these associations vary by ethnic and ethno-religious groups. For this analysis we make use of the new identity measures in the second wave of the UK longitudinal household survey, Understanding Society. We find that ethnic minorities report stronger religious and ethnic identities than the majority, political beliefs are stronger for those with stronger ethnic identity and both these are correlated with regional identities.
Keywords: J15; Z12; Z13; 330; identity; ethnicity; religion; political beliefs; regional identity